International Monetary Fund Annual Report 2015 : Financial Statements. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 2015)
This paper presents different audited financial statements by the IMF. The accompanying consolidated financial statements of the General Department of the IMF ('the Department'), which comprise the consolidated statement of financial position as of April 30,2015, and the related consolidated statement of comprehensive income, of changes in reserves, resources, and retained earnings, and of cash flows for the year then ended have been audited. The responsibility is to express an opinion on the consolidated financial statements based on the audits. The audits have been conducted in accordance with International Standards on Auditing and auditing standards generally accepted in the United States of America. The consolidated financial statements referred to in the paper present fairly, in all material respects, the financial position of the General Department of the IMF on April 30, 2015, and the results of its operations and its cash flows for the year then ended in accordance with International Financial Reporting Standards as issued by the International Accounting Standards Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet